Tinjauan Hukum Pidana Dan Tata Negara Terhadap Pendekatan Filsafat Ilmu Dalam Penanganan Korupsi Di Indonesia - Karimah, Rohmatul; Sari, Sintia Aprilia; Haryadi, Annisa Putri; Tisnanta, HS; Prayoga, Satria (Universitas Sang Bumi Ruwa Jurai, 2025)
Corruption in Indonesia has reached alarming levels and is categorized as an extraordinary crime due to its multidimensional impacts, both economic, political, and social. Corruption eradication has so far been approached primarily through criminal law instruments and state institutions, such as the Corruption Eradication Commission (KPK). However, the fact that corruption rates remain high indicates the need for a more philosophical approach. This article aims to examine corruption eradication in Indonesia through a philosophical perspective encompassing the dimensions of ontology, epistemology, and axiology. This research method uses a normative juridical approach. The sources and types of data used are primary and secondary data. Data collection was conducted through library research. Data processing was carried out by selecting and examining the obtained data for completeness, as well as classifying or grouping the data systematically. The data analysis used is qualitative juridical. The results of this study indicate that corruption eradication cannot be sufficiently understood as an individual crime, but rather as a structural phenomenon that requires modern knowledge methods and a value orientation towards substantive justice, good governance, and constitutional legitimacy. Therefore, it is necessary to increase the independence of law enforcement agencies, epistemological innovation in the field of evidence, anti-corruption ethics education, and a humanistic axiology of law enforcement.